Taking Attention Away from the Auditory Modality: Context-dependent Effects on Early Sensory Encoding of Speech. (1st August 2018) - Xie, Zilong; Reetzke, Rachel; Chandrasekaran, Bharath
Highlights: Visual attention modulates the early sensory encoding of speech signals, as indexed by the frequency-following response. The direction of visual attentional influence is highly contingent on the predictability of the auditory stream. When speech stimulus presentation is less predictable, speech encoding is enhanced with increasing visual attention. When speech stimulus presentation is predictable, speech encoding is reduced with increasing visual attention. Abstract: Increasing visual perceptual load can reduce pre-attentive auditory cortical activity to sounds, a reflection of the limited and shared attentional resources for sensory processing across modalities. Here, we demonstrate that modulating visual perceptual load can impact the early sensory encoding of speech sounds, and that the impact of visual load is highly dependent on the predictability of the incoming speech stream. Participants ( n = 20, 9 females) performed a visual search task of high (target similar to distractors) and low (target dissimilar to distractors) perceptual load, while early auditory electrophysiological responses were recorded to native speech sounds. Speech sounds were presented either in a 'repetitive context', or a less predictable 'variable context'. Independent of auditory stimulus context, pre-attentive auditory cortical activity was reduced during high visual load, relative to low visual load. We applied a data-driven machine learning approach to decode speech sounds from the early auditory electrophysiological responses. Decoding performance was found to be poorer under conditions of high (relative to low) visual load, when the incoming acoustic stream was predictable. When the auditory stimulus context was less predictable, decoding performance was substantially greater for the high (relative to low) visual load conditions. Our results provide support for shared attentional resources between visual and auditory modalities that substantially influence the early sensory encoding of speech signals in a context-dependent manner.